Studi In Silico Prediksi Potensi Senyawa Bahan Alam sebagai Anti-Inflamasi dalam Menghambat COX-2 - Velieana Laurent Sanjaya; Munir Alinu Mulki (Jurnal Sehat Mandiri, 2024)
Infection or tissue injury induces inflammation, which causes pain. Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) are commonly used anti-inflammatory agents but can cause adverse effects on the stomach, kidneys, and liver when used long-term. As a result, efforts have been made to discover new drugs from natural sources to minimize these risks. With advances in technology, the search for new drug candidates using computational modeling, such as molecular docking, has become increasingly common. The aim of this systematic literature review is to predict and evaluate the potential of natural compounds as anti-inflammatory agents through in silico analysis. A systematic literature review of 10 recent articles, selected from an initial 376 articles on the topic of natural plant compounds' anti-inflammatory potential in silico, published between 2020 and 2023, was conducted using the PubMed and Springer databases. The conclusion from the review of the structural analysis of secondary plant metabolites shows that all 45 compounds tested demonstrated the ability to interact with the COX-2 enzyme, which plays a key role in inflammation and pain. Among these compounds, catechin, a member of the flavonoid group, was identified as the best candidate based on in silico analysis.